Retraction: Mouafo Nebot, G.V.; Wang, H. Port Terminal Performance Evaluation and Modeling. Logistics 2022, 6, 10 - Giscard Valonne Mouafo Nebot; Haiyan Wang (Logistics, 2023)
The journal Logistics retracts the article “Port Terminal Performance Evaluation and Modeling” [...]